Determinologization as a Means of Neosemantization of Terms in the Literary Style of the Modern Ukrainian Language (Linguostylistic Studies, 2017)
The article presents comprehensive analysis of the productive determinologization processes at the modern stage of the Ukrainian language development. Vocabulary is quite a dynamic system that undergoes internal and external influence in any language, including Ukrainian. The system is constantly replenished with new words, reflecting changes in the world around us, new realities in the life of a society. The processes of terminologization and determinologization contribute greatly to enriching and updating modern Ukrainian language vocabulary. The word-stock of the Ukrainian language conveys national mentality peculiarities, associated with changes taking place in the political, economic, cultural and social life. Trends and processes occurring in the oral speech penetrate into the system of the national language, are quickly assimilated and find their reflection in the prose works of the late XX – early XXI centuries. The study convincingly testifies that the phenomenon of determinologization is an integral part of these processes.
Keywords: terminologization; determinologization; neosemantization; intellectualization; field/branch terms